Typology: understanding the Bible's promise-shaped patterns : how Old Testament expectations are fulfilled in Christ - Hamilton, James M. (Zondervan Academic, 2022)
"Typology--Understanding the Bible's Promise-Shaped Patterns traces the patterns and similarities between people, events, and institutions in the Bible as they build on one another with escalating significance. It stimulates thought on the relationship between the Testaments and helps readers understand the dynamics of inner-biblical interpretation"--